Immunoresponsive gene 1 modulates the severity of brain injury in cerebral ischaemia. Issue 3 (19th August 2021) - Kuo, Ping-Chang; Weng, Wen-Tsan; Scofield, Barbara A; Furnas, Destin; Paraiso, Hallel C; Yu, I-Chen; Yen, Jui-Hung
Abstract: Inflammatory stimuli induce immunoresponsive gene 1 expression that in turn catalyses the production of itaconate through diverting cis -aconitate away from the tricarboxylic acid cycle. The immunoregulatory effect of the immunoresponsive gene 1/itaconate axis has been recently documented in lipopolysaccharide-activated mouse and human macrophages. In addition, dimethyl itaconate, an itaconate derivative, was reported to ameliorate disease severity in the animal models of psoriasis and multiple sclerosis. Currently, whether immunoresponsive gene 1/itaconate axis exerts a modulatory effect in ischaemic stroke remains unexplored. In this study, we investigated whether immunoresponsive gene 1 plays a role in modulating ischaemic brain injury. In addition, the molecular mechanism underlying the protective effects of immunoresponsive gene 1 in ischaemic stroke was elucidated. Our results showed that immunoresponsive gene 1 was highly induced in the ischaemic brain following ischaemic injury. Interestingly, we found that IRG1 −/− stroke animals exhibited exacerbated brain injury, displayed with enlarged cerebral infarct, compared to wild-type stroke controls. Furthermore, IRG1 −/− stroke animals presented aggravated blood–brain barrier disruption, associated with augmented Evans blue leakage and increased immune cell infiltrates in the ischaemic brain. Moreover, IRG1 −/− stroke animals displayed elevated microglia activation, demonstrated with increased CD68, CD86 and Iba1 expression. Further analysis revealed that immunoresponsive gene 1 was induced in microglia after ischaemic stroke, and deficiency in immunoresponsive gene 1 resulted in repressed microglial heme oxygenase-1 expression and exacerbated ischaemic brain injury. Notably, the administration of dimethyl itaconate to compensate for the deficiency of immunoresponsive gene 1/itaconate axis led to enhanced microglial heme oxygenase-1 expression, alleviated ischaemic brain injury, improved motor function and decreased mortality in IRG1 −/− stroke animals. In summary, we demonstrate for the first time that the induction of immunoresponsive gene 1 in microglia following ischaemic stroke serves as an endogenous protective mechanism to restrain brain injury through heme oxygenase-1 up-regulation. Thus, our findings suggest that targeting immunoresponsive gene 1 may represent a novel therapeutic approach for the treatment of ischaemic stroke. Abstract : Kuo et al. reported that the induction of immunoresponsive gene 1 may serve as an endogenous protective mechanism to restrain brain injury following ischaemic stroke. Thus, their study suggests that targeting immunoresponsive gene 1 may represent a novel therapeutic approach for the treatment of ischaemic stroke. Graphical Abstract: Video Abstract: